ANALISIS KONSUMSI BAHAN BAKAR ALAT ANGKUT UD QUESTER CWE 370 DALAM KEGIATAN PENGANGKUTAN BIJIH NIKEL - Hendra Rujiadi Adha (PERHAPI, 2023)
PT. X is a mining contractor company located in North Morowali Regency, Central Sulawesi Province. Transport activities use a combination of excavator PC300 and UD Quester CWE370. Based on the results of the study, there are several haul road geometries that do not meet the standards that have a road slope of more than 8%. Other factors that affect the increase in fuel consumption are; acceleration, RPM, engine brake horsepower and workload. The problem that appear is that the consumption and/or fuel ratio exceeds the company's standards, data recorded in March 2021 that the consumption and fuel ratio of transportation equipment reached 13.63 liters/hour and 0.47 liters/BCM from the company standard of 8 liters/hour and 0.27 liters/BCM. The analysis was conducted to determine the effect of haul road conditions on the fuel consumption of conveyances. The theoretical calculation of fuel consumption is carried out using two methods, that is based on rimpul and RPM. It is known that fuel consumption based on rimpul calculation is 12.10 liters/hour, while based on RPM is 18.84 liters/hour. After making improvements to the geometry of the road will reduce fuel consumption and increase productivity. Based on these calculations and recommendations, fuel consumption uses rimpul calculations, namely; 12.45 liters/hour, while the fuel ratio is 0.28 liters/BCM..